Barriers of the Development of the European Union's Exports to Japan - Pasierbiak, Paweł (Bariery rozwoju eksportu Unii Europejskiej do Japonii, 2010)
The author has focused on a task to indicate barriers which reduce European Union's exports to Japan within the period of 2000-2009. Traditionally existing structural barriers have been losing their importance, while tariffs also do not constitute the main obstacle to exports. Main impediments come from utilization of non-tariff measures. Japanese norms, standards, certification procedures and a lack of acceptance of evaluations made by the EU exporters or international bodies form an efficient barriers in the development of the EU's exports to Japan. A reduction of these barriers could implicate a strong welfare effect as the value of exports would increase.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 126, s. 306-315
Keywords: international trade; trade barriers; foreing trade policy